Sciatic T‐cell neurolymphomatosis in a dog. Issue 1 (2nd May 2014) - Rupp, Angie; Ives, Edward; Rudorf, Heike; Constantino‐Casas, Fernando
Abstract : Infiltration of peripheral nerves distal to the plexus by neoplastic lymphocytes has been rarely reported in dogs; only one previous case report describes B‐cell infiltration of the femoral nerve. A 4.5‐year‐old female cross‐breed dog presented with a three‐week history of tail flaccidity, tenesmus, anorexia and progressive monoparesis of the right pelvic limb. Ultrasound imaging revealed a thickened gastric wall and a large mass at the root of the mesentery. MRI demonstrated enlargement of the right L6 and L7 spinal nerve roots and thickening of the proximal aspect of the right sciatic nerve. Postmortem histopathology of stomach, mesenteric mass, right L7 spinal nerve and sciatic nerve revealed marked infiltration with sheets of CD3‐positive cells, consistent with a diagnosis of T‐cell lymphoma. The spinal cord appeared to be free from infiltrates.